Perturbation of n dimensional AQ - mixed type functional equation via Banach spaces and Banach algebra : Hyers direct and alternative fixed point methods - Arunkumar, M. (International Journal of Advanced Mathematical Sciences, 2014)
In this paper, the authors obtain the general solution and generalized Ulam - Hyers stability of n dimensional additive quadratic functional equation in Banach spaces using direct and fixed point methods. We also investigate the stability of the above  equation in Banach algebra using direct and fixed point approach.